Are trade preferences a panacea? The African growth and opportunity act and African exports - Ana Margarida Fernandes; Hibret Maemir; Aaditya Mattoo; Alejandro Forero (Center for Economic Studies and ifo Institute (CESifo), 2019)
Does "infant industry" preferential access durably boost export performance? This paper exploits significant trade policy changes in the United States (US) to address this question. The expansion of Generalized System of Preferences (GSP) products for less developed countries in 1997 and the African Growth and Opportunity Act (AGOA) in 2001 are used to assess whether preferential access boosts exports of eligible products in general and apparel specifically. The end of the Multi-Fiber Arrangement (MFA) in 2005 is used to assess whether apparel export expansions survived the erosion of preferences. To find a causal impact of these changes, we use a triple-differences regression and 26 years of newly constructed trade and tariff data at the country-product-year level (1992-2017). The analysis finds that AGOA boosted African apparel exports and the GSP expansion increased African exports of other eligible products. While the marginal impacts on African apparel exports grew sharply in the first AGOA years, they leveled off after 2005, when the MFA end unleashed competition from Asian countries. The illusion of sustained African apparel exports is created by late-bloomers in East Africa offsetting boom-bust patterns in Southern Africa and insignificant responses in Central and West Africa. Firm-level customs data reveal that even in East Africa the recent export growth was driven by new entrants rather than incumbent firms whose competitiveness might have been nurtured by the big preference margins in the early AGOA period. Preferential access per se was not sufficient but needed to be complemented by specific domestic reforms: tariff liberalization, reduced regulatory burden, and enhanced connectivity.
Keywords: F13; F14; F68; O20; O55; 330; tariff preferences; Africa; AGOA; GSP; exports; MFA